Reproductive ability of cows of domestic dairy breeds with different allelic variants of the leptin gene - A. D. Lemyakin; A. N. Tyazhchenko; K. D. Sabetova; A. A. Chaitsky; P. O. Shchegolev; A. A. Korolev (Аграрная наука Евро-Северо-Востока, 2022)
Conducting genetic studies of domestic local breeds of cattle is relevant due to the fact that they are carriers of valuable economic traits and have a high adaptive ability to local conditions. The aim of the research is to study the association of polymorphic variants of the leptin gene with the reproductive ability of cattle of the Kostroma, Black-and-White and Yaroslavl breeds bred in the Kostroma region. Genotyping was performed by real-time polymerase chain reaction (RT-PCR) using HRM analysis. It was found that in the Kostroma and Yaroslavl breeds, the AV genotype (0.546 and 0.452, respectively) had the highest frequency for the LEP-A80V locus, and the AA genotype (0.550) in the Black-and-White breed. In terms of polymorphism Y7F of the leptin gene, the YY genotype prevailed among animals of all the studied breeds of cows. For the LEP-R25C locus, the highest frequency of occurrence was recorded in individuals with the RC genotype (0.486), while in cattle of the Yaroslavl and Black-and-White breeds, the RR genotype (0.690 and 0.483, respectively). However, no statistically significant differences were found in terms of reproductive ability between cows of different genotypes for the leptin gene. There is reason to believe that in cattle of the Kostroma breed the desired genotype is AV, in Yaroslavl cattle it is AA (LEP-A80V), and in Black-and-White cattle it is RR (LEP-R25C). The observed tendencies towards the presence of higher reproductive qualities in the carriers of the LEP-A80VA and LEP-R25CR alleles in the studied cattle breeds are confirmed by the studies of other authors. Therefore, the study of the effect of leptin gene polymorphism on the reproductive abilities of cows of domestic dairy breeds must be continued with the involvement of a significantly larger number of animals.